Expression of CD55, CD59, and CD35 on red blood cells of β-thalassaemia patients - Kurtoğllu, Ayşegül Uğur; Koçtekin, Belkls; Kurtoğlu, Erdal; Yildiz, Mustafa; Bozkurt, Selen (Central-European journal of immunology, 2017)
-thalassaemia ( -Thal) is considered a severe, progressive haemolytic anaemia, which needs regular blood transfusions for life expectancy. Complement-mediated erythrocyte destruction can cause both intravascular and extravascular haemolysis. Complement regulatory proteins protect cells from such effects of the complement system. We aimed to perform quantitative analysis of membrane-bound complement regulators, CD55 (decay accelerating factor - DAF), CD35 (complement receptor type 1 - CR1), and CD59 (membrane attack complex inhibitory factor - MACIF) on peripheral red blood cells by flow cytometry. The present study was carried out on 47 -thalassemia major ( -TM) patients, 20 -thalassaemia intermedia ( -TI) patients, and 17 healthy volunteers as control subjects. CD55 levels of -TM patients (58.64 ±17.06%) were significantly decreased compared to -TI patients (83.34 ±13.82%) and healthy controls (88.57 ±11.69%) (p < 0.01). CD59 levels of -TM patients were not significantly different than -TI patients and controls, but CD35 levels were significantly lower in the -TM patients (3.56 ±4.87%) and -TI patients (12.48 ±9.19%) than in the control group (39.98 ±15.01%) (p < 0.01). Low levels of CD55 and CD35 in thalassaemia major patients indicates a role for them in the aetiopathogenesis of haemolysis in this disease, and also this defect in a complement system may be responsible for the chronic complications seen in these patients.